E-Sanction Policy In Online Learning In Universities Based On Cyber Education Service System - Yana Indawati; Hervina Puspitosari; Yovita Arie Mangesti (International Journal of Educational Research & Social Sciences, 2021)
The rapid globalization of technology, coupled with the pace of technological development, has become an online learning facility that makes it easier to meet face-to-face virtually in the current learning system. Online learning expects students to gain soft skills in the current digital era, especially supported by various Merdeka Campus programs. The E-Sanction policy is a product that is needed with the shift in education in today's digital era. Improvement of the education system based on cyber- service system services. This research is collaborative research between the lecturers of the Universitas Pembangunan Nasional “Veteran” Jawa Timur and the Universitas 17 Agustus  1945 as a higher education institution where researchers teach who have also responsively eliminated face-to-face teaching and learning on campus since the Covid 19 pandemic to suppress the growth of exposure to the Corona 19 virus that becomes a global problem. From the results of this study, it is possible to obtain an overview of the effectiveness of online learning and obtain an e-sanction policy model that can be applied to students so that lectures can run in an orderly manner. Every university has a code of ethics that applies to students and along with online learning conditions, it is necessary to set a code of ethics policy for students in participating in the online learning process. The need for e-sanction applicateions as a means of providing sanctions for violations of the student code of ethics.